Review of laser diagnostics at the Vulcan laser facility. (2015) - Musgrave, Ian; Galimberti, Marco; Boyle, Alexis; Hernandez-Gomez, Cristina; Kidd, Andrew; Parry, Bryn; Pepler, Dave; Winstone, Trevor; Collier, John
Abstract : In this paper we review the provision of the laser diagnostics that are installed on the Vulcan laser facility. We will present strategies for dealing with the energy of high energy systems and with ways of handling the beam sizes of the lasers. We present data captured during typical experimental campaigns to demonstrate their reliability and variation in shot to shot values.